CONJUGACY CLASS SIZES OF SUBGROUPS AND THE STRUCTURE OF FINITE GROUPS - Han, Zhangjia; Shi, Huaguo (Italian Journal of Pure and Applied Mathematics, 2014)
The authors investigate the influences of conjugacy class sizes of subgroups of a finite groups G on the structure of G. Some suﬃcient conditions for a finite group to be p-nilpotent, p- solvable and supersolvable are obtained.